2019
DOI: 10.1002/oby.22522
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Experiences of African American, Hispanic, and Non‐Hispanic White Men and Women with Type 2 Diabetes: The Look AHEAD Trial

Abstract: Objective: The aim of this study was to characterize weight loss, treatment engagement, and weight control strategies utilized by African American, Hispanic, and non-Hispanic white participants in the Action for Health in Diabetes (Look AHEAD) Intensive Lifestyle Intervention by racial/ethnic and sex subgroups. Methods: Weight losses at 1, 4, and 8 years among 2,361 adults with obesity and type 2 diabetes randomized to intervention (31% minority; 42% men) are reported by subgroup. Multivariable models within s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…After 8 years of intervention, all female patients from different ethnic groups lost weight similarly [30]. Among men, there was a trend toward less weight loss among African American and Hispanic men compared with Whites [30].…”
Section: Management Of Diabetes Among Minoritiesmentioning
confidence: 93%
See 2 more Smart Citations
“…After 8 years of intervention, all female patients from different ethnic groups lost weight similarly [30]. Among men, there was a trend toward less weight loss among African American and Hispanic men compared with Whites [30].…”
Section: Management Of Diabetes Among Minoritiesmentioning
confidence: 93%
“…Lifestyle intervention: In 'The Action for Health in Diabetes (Look Ahead)" trial, 5,145 (36% minorities, 40% men) overweight/ obese subjects with type 2 diabetes were randomized to intensive lifestyle intervention and a control group of diabetes support and education [30]. The objective of the lifestyle intervention is a weight loss of 10% by decreased caloric and fat intake and increased physical activity [30]. After 8 years of intervention, all female patients from different ethnic groups lost weight similarly [30].…”
Section: Management Of Diabetes Among Minoritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our decision to focus our review on Hispanic women living in the USA stems from the knowledge that U.S. Hispanic women have unique attitudes, barriers, and facilitators related to weight loss with important socio-cultural contextual factors specific to the USA (e.g., acculturation, built environment, high burden of obesity, and related disease) meriting focused examination. Additionally, racial/ethnic- and sex-specific models exploring predictors of weight loss have demonstrated differences in key predictors of weight loss, further justifying the need to independently focus on Hispanic women [20].…”
Section: Methods and Analysismentioning
confidence: 99%
“…Although DPP was a large trial, only 16% ( n = 154) of the intensive lifestyle intervention (ILI) group identified as Hispanic women and information including level of acculturation, years in the USA, and country of origin were not collected, thereby limiting generalizability to different sub-populations within the Hispanic community [16]. In the Look AHEAD trial, the longest randomized trial to evaluate the effectiveness of lifestyle modification on weight and cardiovascular-related health outcomes, Hispanic women comprised only 9% ( n = 240) of participants in the ILI group and weight loss achieved by year 1 was slowly regained over the next 3 to 7 years, including among Hispanic women [19, 20]. Additionally, similar to the DPP, the multicomponent lifestyle intervention delivered to participants makes it difficult to ascertain which specific intervention components were effective in inducing the observed weight loss.…”
Section: Introductionmentioning
confidence: 99%